Student perceptions about interprofessional education after an elective course. Issue 4 (July 2015) - Gunaldo, Tina Patel; Andrieu, Sandra Carlin; Garbee, Deborah; Giovingo, Lauren K.; Mercante, Donald E.; Tortu, Stephanie; English, Robin
Abstract A growing body of evidence indicates interprofessional collaborative practice improves patient care. With this in mind, Louisiana State University Health Sciences Center formally committed to expanding interprofessional education (IPE) initiatives. Thirty-eight self-selected students enrolled in an IPE elective course during the fall of 2012. Students completed the Readiness for Interprofessional Learning Scale (RIPLS) pre- and post-course and also completed a post-course survey. Results indicated a significant change in the roles and responsibilities scale of the RIPLS. Analysis of the data from the post-course survey demonstrated students were able to identify key terms of an IPE definition, as related to their learning experience. In addition, themes of communication, learning/increased knowledge, and collaboration/contribution of other health care professionals were noted across all questions in the post-course survey. Based on the results of this study, an elective course is a promising educational opportunity to increase awareness and knowledge of IPE within academic medical centers.